The art of painting rainbows—between color science and painter's practice. Issue 6 (16th July 2022) - Kirchner, Eric; Koken, Phil
Abstract: We present the first quantitative analysis of representing rainbow colors in historical paintings from Antiquity to the twentieth century. Using high‐resolution photographs of art works we determined and analyzed percentages of areas from painted rainbows covered by different color categories. Our results are the first to quantitatively show that up to the nineteenth century, painters generally did not follow contemporary color theories when painting rainbows. The only evidence of an influence from color theory on painted rainbows is the use of a color scheme consisting of three primary and three secondary colors as described by d'Aguilon (1613) and others. For painting rainbows, this scheme was used for the first time in the early nineteenth century, rising to 6% of all paintings created during that century, and reaching 24% in the twentieth century. We conclude that in the vast majority of paintings, individual color choices by the painter were decisive. Additionally, we identified a few weak trends: (1) color combinations in painted rainbows over time gradually become slightly more similar to the color proportions in natural rainbows; (2) from the Renaissance onward, circa 35%–40% of the painted rainbows consist of orange, yellow and green, sometimes with white as well. This trend may originate from Antiquity; (3) Already from Antiquity a white band was used as an artistic but unrealistic device to create the impression of a luminous arc. This trend reached its maximum in popularity in Baroque, but it is still used in many painted rainbows up to the twentieth century. Abstract : Rainbow in John Constable, Salisbury Cathedral from the Meadows, 1831